Analisis produktivitas departemen servis pada PT TI dengan Metode Objective Matrix (Omax) - Maulana, Eko; Perdana, Surya (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2020)
PT IT is a company engaged in the air system facilities industry, the company experienced an up-and-downphase in the company's productivity in 2019. To deal with an existing problem in the company used the ObjectiveMatrix (Omax) method. The method will discuss the performance criteria that have a weight value to be usedas a measure of productivity in the company and the criteria that will be combined into one in a particularworking group into a matrix. The result of this study is that the company experienced an up-and-down phasethat in June 2019 experienced an increase in demand in maintenance chiller jobs with low main hours.Meanwhile, in May 2019 the company experienced a decrease caused by chiller units done by technicians quitea bit and the number of complaints from customers because they were dissatisfied with the workers worked bytechnicians. In addition, it is also known that some criteria are used to measure the value of productivity weightssuch as man hours criteria, water criteria, electricity criteria, material criteria and quality criteria. As for thecriteria that contribute less in productivity improvement that contributes to the decrease in productivity of thecompany is the criteria 3 namely the use of water energy with a score of 35. From the results obtained, thecompany will provide counseling to each employee at the time of the evaluation of work.